A new species of genus Neoaloa Singh & Kirti, 2015 from Bihar, India (Lepidoptera: Erebidae: Arctiinae: Arctiini) - Singh, Navneet; Joshi, Rahul; Ahmad, Jalil (Zootaxa, 2018)
A new species, Neoaloa cernyi Singh & Joshi, sp. nov. is described from Gular-Ghat of Valmiki Tiger Reserve, Bihar, India. Additionally, the original combination of Aloa collaris Hampson, 1891, comb. rev. is restored.